Unit policies regarding tocolysis after preterm premature rupture of membranes: association with latency, neonatal and 2-year outcomes (EPICE cohort) - Lorthe, E (2020)
After preterm premature rupture of membranes (PPROM), antibiotics and antenatal steroids are effective evidence-based interventions, but the use of tocolysis is controversial. We investigated whether a unit policy of tocolysis use after PPROM is associated with prolonged gestation and improved outcomes for very preterm infants in units that systematically use these other evidence-based treatments. From the prospective, observational, population-based EPICE cohort study (all very preterm births in 19 regions from 11 European countries, 2011–2012), we included 607 women with a singleton pregnancy and PPROM at 24–29 weeks’ gestation, of whom 101, 195 and 311 were respectively managed in 17, 32 and 45 units with no-use, restricted and liberal tocolysis policies for PPROM. The association between unit policies and outcomes (early-onset sepsis, survival at discharge, survival at discharge without severe morbidity and survival at two years without gross motor impairment) was investigated using three-level random-intercept logistic regression models, showing no differences in neonatal or two-year outcomes by unit policy. Moreover, there was no association between unit policies and prolongation of gestation in a multilevel survival analysis. Compared to a unit policy of no-use of tocolysis after PPROM, a liberal or restricted policy is not associated with improved obstetric, neonatal or two-year outcomes.